Residential end-use electricity demand. Development over time - Hanne Marit Dalen; Bodil M. Larsen (Statistics Norway, Research Department, 2013)
It is costly and difficult to meter electricity consumption for different end uses, e.g. space heating, lighting and household appliances. We deduce a model for using cross-sectional data for total annual electricity consumption for a sample of households, together with information from energy surveys, to estimate the end uses within an econometric demand model conditional on appliance ownership. By applying a consistent method to Norwegian data for 1990, 2001 and 2006, we compare results over time and detect possible trends. We find that electricity consumption for many end use necessities such as washing, water heating and refrigeration varies somewhat from year to year, but they show no trend. The only clear trend is a steady increase in electricity used for more untraditional end uses and newer types of appliances. Total energy consumption for heating purposes is quite stable over the time period.
Keywords: C51; D12; Q40; 330; Energy end-use consumption over time; Econometric conditional demand model